2021
DOI: 10.5194/wcd-2021-38
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of deep convection representation in a global atmospheric model on the warm conveyor belt and jet stream during NAWDEX IOP6

Abstract: Abstract. The effect of parameterized deep convection on warm conveyor belt (WCB) activity and jet stream is investigated by performing simulations of an explosively-developing large-scale cyclone that occurred during the North Atlantic Waveguide and Downstream Impact Experiment (NAWDEX) field campaign using the Météo-France global atmospheric model ARPEGE. Three simulations differing only from their deep convection representation are analysed. The first one was performed with the Bougeault et al. (1985) schem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…The parametrisation schemes that contribute the most to the diabatic heating during the ascent of WCBs are the microphysics and convection schemes (Joos and Forbes, 2016). Several studies show that WCBs and their impact on the upper‐level jet stream are sensitive to the choice of parametrisation schemes (Joos and Wernli, 2012; Joos and Forbes, 2016; Maddison et al ., 2020; Mazoyer et al ., 2021; Rivière et al ., 2021), and systematic errors in the upper‐level Rossby‐wave structure are linked to uncertainties in the parametrisations of diabatic processes (Gray et al ., 2014; Martínez‐Alvarado et al ., 2016). Also other weather systems, such as (recurving) tropical cyclones and mesoscale convective systems, are associated with rapidly ascending air streams and are driven by the release of latent heat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parametrisation schemes that contribute the most to the diabatic heating during the ascent of WCBs are the microphysics and convection schemes (Joos and Forbes, 2016). Several studies show that WCBs and their impact on the upper‐level jet stream are sensitive to the choice of parametrisation schemes (Joos and Wernli, 2012; Joos and Forbes, 2016; Maddison et al ., 2020; Mazoyer et al ., 2021; Rivière et al ., 2021), and systematic errors in the upper‐level Rossby‐wave structure are linked to uncertainties in the parametrisations of diabatic processes (Gray et al ., 2014; Martínez‐Alvarado et al ., 2016). Also other weather systems, such as (recurving) tropical cyclones and mesoscale convective systems, are associated with rapidly ascending air streams and are driven by the release of latent heat.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies show that WCBs and their impact F I G U R E 1 One-hr accumulated temperature tendencies due to parametrisations (shading every 0.1 K⋅h −1 ) averaged over the model levels 105-96 (approx. 700-500 hPa) from the ERA5 short-term forecast initialised at 1800 UTC on March 8, 2016 at lead time 6 hr and rapidly ascending air streams (ascent of at least 600 hPa in 48 hr) in their ascending stage between 800 and 400 hPa from ERA5 reanalysis data valid at 0000 UTC on March 9, 2016 (green contour), identified by trajectory analysis as explained in Section 2 [Colour figure can be viewed at wileyonlinelibrary.com] on the upper-level jet stream are sensitive to the choice of parametrisation schemes (Joos and Wernli, 2012;Joos and Forbes, 2016;Maddison et al, 2020;Mazoyer et al, 2021;Rivière et al, 2021), and systematic errors in the upper-level Rossby-wave structure are linked to uncertainties in the parametrisations of diabatic processes (Gray et al, 2014;Martínez-Alvarado et al, 2016). Also other weather systems, such as (recurving) tropical cyclones and mesoscale convective systems, are associated with rapidly ascending air streams and are driven by the release of latent heat.…”
Section: Introductionmentioning
confidence: 99%
“…Flack et al (2021) investigated how a decrease in the grid spacing from 150 to 50 km affects diabatic processes and the intensification of extratropical cyclones and concluded that the relative importance of diabatic heating remains unchanged, and model improvement equally results from a better representation of dynamics. Wimmer et al (2022) and Rivière et al (2021) found that the representation of deep convection substantially affects diabatic processes, the WCB activity and the vertical structure of the jet stream. In particular, Rivière et al (2021) showed that WCB ascents are quick and abrupt with explicit deep convection but slow and long-lived for parameterized deep convection.…”
Section: Introductionmentioning
confidence: 99%
“…The PV and potential temperature (θ) Lagrangian framework can be used to explain atmospheric circulation differences between simulations performed with distinct models or between sensitivity numerical experiments made with the same model but using different parameterization schemes Joos and Forbes, 2016;Mazoyer et al, 2021;Rivière et al, 2021). Joos and Forbes (2016) used this approach to compare two simulations of the ECMWF-IFS global model with distinct cloud microphysics schemes.…”
Section: Introductionmentioning
confidence: 99%
“…At 24 h-48 h lead time, the PV and wind speed differences were already well marked and anomalies span an extended band along the western edge of the ridge due to different heating rates within the WCB. The PV-θ framework has been also used to analyze WCB differences and impact on the tropopause with different deep convection parameterization schemes Rivière et al, 2021) but the amplitude of the impact on the upper-level circulation varies from case to case. found rather modest differences in the tropopause location after 24 h for a moderate cyclone between reduced and intense parameterized convection while Rivière et al (2021) found important differences with a jet stream shift of a few hundred kilometers after 24 h for an explosive cyclone.…”
Section: Introductionmentioning
confidence: 99%